2008
DOI: 10.1002/eat.20479
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in weight control practices among U.S. adolescents from 1995 to 2005

Abstract: Objective: To examine trends in weight control practices from 1995 to 2005. Method: The Youth Risk Behavior Surveillance System biennially assesses five weight control behaviors among nationally representative samples of United States high school students. Results: Across time, more females than males dieted (53.8% vs. 23.8%), used diet products (10% vs. 4.3%), purged (7.5% vs. 2.7%), exercised (66.5% vs. 46.9%), or vigorously exercised (42.8% vs. 36.8%). All weight control behaviors among males increased duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 45 publications
2
42
3
Order By: Relevance
“…That is, the majority of African American women in this study discussed how perceptions of their body image were influenced by their level of comfort, satisfaction, and happiness with themselves rather than by weight or specific body parts. This is partially consistent with research reports highlighting the fact that African American women consistently display higher levels of body satisfaction, weight satisfaction, and heavier body ideals when compared with women from other racial and ethnic groups (Befort, Thomas, Daley, Rhode, & Ahluwalia, 2008;Chao et al, 2008;Grabe & Hyde, 2006;Kronenfeld et al, 2010;Shoneye, Johnson, Steptoe, & Wardle, 2011). However, although the women in this study reported being internally motivated regarding their body image, the majority of African American women in this study also discussed how some external factors (e.g., media, family, men) equally influenced their views of their body image.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…That is, the majority of African American women in this study discussed how perceptions of their body image were influenced by their level of comfort, satisfaction, and happiness with themselves rather than by weight or specific body parts. This is partially consistent with research reports highlighting the fact that African American women consistently display higher levels of body satisfaction, weight satisfaction, and heavier body ideals when compared with women from other racial and ethnic groups (Befort, Thomas, Daley, Rhode, & Ahluwalia, 2008;Chao et al, 2008;Grabe & Hyde, 2006;Kronenfeld et al, 2010;Shoneye, Johnson, Steptoe, & Wardle, 2011). However, although the women in this study reported being internally motivated regarding their body image, the majority of African American women in this study also discussed how some external factors (e.g., media, family, men) equally influenced their views of their body image.…”
Section: Discussionsupporting
confidence: 90%
“…Given the increased reports of eating, body image, appearance, and weight concerns in African American women (Capodilupo & Kim, 2013;Chao et al, 2008;Poran, 2006; and the multiple contextual factors that may influence how and why these behaviors are manifested, it is imperative that the concerns of African American women are represented. Five salient themes about African American women's experiences with eating, body image, and overall appearance emerged from our data perceptions of body image (self, media, peers, family, significant others), challenges with body image, perceptions of eating attitudes and behavior (self, health-related influences, childhood/family influence), the role of food as comfort, and perceptions of overall appearance (self, family, media).…”
Section: Discussionmentioning
confidence: 98%
“…Bearing in mind the caveat that symptom prevalence cannot be used to extrapolate full syndrome estimates, we note that in epi- demiological studies of adolescent samples, ethnic differences for purging behavior were found to be either nonsignificant 52 or significant only when comparing black girls with Hispanic girls (the latter reporting higher rates). 53 Overall, studies indicate that Purging Disorder is not restricted to any particular racial or ethnic subgroup. However, larger epidemiological studies are required to examine whether some groups are over or underrepresented among those with Purging Disorder.…”
Section: Who Most Likely Presents With Purging Disorder?mentioning
confidence: 97%
“…Our prior research has not found racial/ethnic differences in adult gay and bisexual men’s body image, though there were differences in disordered eating scores with White and Latino men evidencing higher scores (Siconolfi et al, 2009). Data from the Youth Risk Behavior Surveillance System (YRBSS) have also indicated that Hispanic young men were more likely than their peers to engage in weight control (Chao et al, 2008). There is a paucity of analyses examining racial/ethnic differences in body image and body dissatisfaction among both young and adult sexual minority men, likely attributable to predominately White samples in the existing research (Brennan et al, 2012, 2013).…”
Section: Introductionmentioning
confidence: 99%